Immunohistochemical Detection of Cryptosporidium-Induced Intestinal Tissue Alterations in Dexamethasone Treated & Un-Treated Mice - Hagar F. Abdelmksoud (Journal of Global Pharma Technology, 2018)
Cryptosporidium parvum (C. parvum) is coccidian protozoan that causes cryptosporidiosis, a parasitic disease of the mammalian intestinal tract.  C. parvum is considered one of the most important waterborne pathogen among the most relevant parasitic enteric agents in man and animals. It is resistant to all practical levels of chlorination and it is an obligate intracellular pathogen. It has been the cause of multiple diarrhea outbreaks in developed and developing countries. The present work was carried out to evaluate the pathological, immuno-histochemical and molecular changes in the ileocecal region induced by chronic irritation with different inoculum sizes of cryptosporidium (50,500 oocysts) in immunocompetent and immunosuppressed mice. The mice were euthanized at different dates starting from 14, 21, 36, 45, 57 till day 64 to study these transformations. Histopathological examination of the ileocecal region revealed neoplastic changes in the form of dysplasia, polypoid structures, architectural distortion, glandular crowding, marked cellular atypia, exophytic adenomatous polypi, intramuscular adenocarcinoma and marked nuclear anaplasia. Immunohistochemical results showed positive K-ras expression. The present study proved that Cryptosporidium species is one of the infectious agents that may induce intestinal neoplasia, which is highly affected by repeated exposure and elevated parasite loads.Keywords: Cryptosporidium Mice, Intestinal tissue alterations, Histopathology, Immunohistochemistry.